2020
DOI: 10.1109/access.2020.3025590
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Irrigation Scheduling System Using Low-Cost Wireless Sensor Network Toward Sustainable and Precision Agriculture

Abstract: Agricultural irrigation developments have gained attention to improve crop yields and reduce water use. However, traditional irrigation requires excessive amounts of water and consumes high electrical energy to schedule irrigations. This paper proposes a fuzzy-based intelligent irrigation scheduling system using a low-cost wireless sensor network (WSN). The fuzzy logic system takes crop and soil water variabilities into account to adaptively schedule irrigations. The theoretical crop water stress index (CWSI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 45 publications
1
50
1
Order By: Relevance
“…The integrated control system identifies the maximum efficiency point and the minimum energy consumption in the entire irrigation system using a decision matrix which takes into account the pumping cost, the pumping group efficiency and the total flow required at a constant pressure. This is in contrast to previous studies that consider soil moisture, [9], air temperature and solar radiation, [10] irrigation water withdrawal in [11] and pump speed and flow in [12].…”
Section: Introductioncontrasting
confidence: 68%
“…The integrated control system identifies the maximum efficiency point and the minimum energy consumption in the entire irrigation system using a decision matrix which takes into account the pumping cost, the pumping group efficiency and the total flow required at a constant pressure. This is in contrast to previous studies that consider soil moisture, [9], air temperature and solar radiation, [10] irrigation water withdrawal in [11] and pump speed and flow in [12].…”
Section: Introductioncontrasting
confidence: 68%
“…The current study of WSN is also focused on incorporating intelligence in the process of irrigation in PA. The work carried out by Jamroen et al [85] has developed an irrigation scheduling mechanism using fuzzy logic in WSN. The outcome witnessed an increase in crop yield.…”
Section: Wsn In Precision Agriculturementioning
confidence: 99%
“…In recent years, studies on wireless sensor networks (WSNs) have demonstrated their effectiveness for many remote sensing applications including precision agriculture [1][2][3], logistics carrier monitoring [4], industrial monitoring and control [5], underground coal mines monitoring [6,7], monitoring forest fire [8,9], monitoring seismic activity [10], marine environment monitoring [11], etc. The major advantage of WSNs technology is that it is ad-hoc and easy to manage and configure.…”
Section: Introductionmentioning
confidence: 99%